1984
DOI: 10.1111/j.1365-2265.1984.tb00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Glomerulosa Failure in Congenital Adrenocortical Unresponsiveness to Acth

Abstract: We report two children of a family with congenital adrenocortical unresponsiveness to ACTH. Repeated stimulation of the adrenal by Synthetic 1-24 ACTH (Synacthen) failed to increase cortisol secretion, but produced significant rises of serum aldosterone. This was, however, associated with increased plasma renin activity. Only when the renin-angiotensin effect was eliminated, by a converting enzyme blocker, did Synacthen fail to affect serum aldosterone. These data support the view that glucocorticoid deficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 10 publications
3
15
0
Order By: Relevance
“…Hypothyroidism was detected through the national neonatal screening program and showed high blood TSH and low total thyroxine (T4) values. These were confirmed by serum measurements of TSH greater than 100 mU/L (normal range 0.5-6) and free thyroxine (FT4) of 1.2-7.0 pmol/L (normal [11][12][13][14][15][16][17][18][19][20][21][22][23][24] prior to the institution of treatment with levothyroxine (LT4) (Fig. 1).…”
Section: Patientsmentioning
confidence: 88%
See 1 more Smart Citation
“…Hypothyroidism was detected through the national neonatal screening program and showed high blood TSH and low total thyroxine (T4) values. These were confirmed by serum measurements of TSH greater than 100 mU/L (normal range 0.5-6) and free thyroxine (FT4) of 1.2-7.0 pmol/L (normal [11][12][13][14][15][16][17][18][19][20][21][22][23][24] prior to the institution of treatment with levothyroxine (LT4) (Fig. 1).…”
Section: Patientsmentioning
confidence: 88%
“…Characteristically, serum cortisol levels are low or undetectable and ACTH concentrations are high. Cortisol and aldosterone do not respond to exogenous ACTH but aldosterone retains a normal response to activation of the reninangiotensin axis by salt and posture changes (19)(20)(21). The zona fasciculata-reticularis of adrenal cortex is atrophied whil the zona glomerulosa is well preserved (18,19).…”
mentioning
confidence: 92%
“…Plasma ACTH is increased but the adrenal fasciculata and glomerulosa are unresponsive to ACTH (9). Every single one and the totality of these components may affect the physiological response to stress.…”
mentioning
confidence: 99%
“…ACTH levels of above 1,000 pg/ml (normal range <80 pg/ml by RIA; <50 pg/ml by IRMA) are commonly found [8, 23]. Occasionally, children may have minor impairment of the renin-angiotensin-aldosterone axis at the time of initial presentation [8, 24]. The physiological explanation of this observation is unclear.…”
Section: Clinical and Biochemical Features Of Fgdmentioning
confidence: 99%
“…Firstly, there is evidence that ACTH directly activates the production of aldosterone in the zona glomerulosa (ZG). It has been found that MC2R mRNA localizes to the ZG and administration of synthetic ACTH to normal human subjects results in a rise in plasma aldosterone levels [5,24,25,26,27]. The physiological importance of ACTH-dependent regulation of aldosterone in normal physiology and disease is undetermined.…”
Section: Clinical and Biochemical Features Of Fgdmentioning
confidence: 99%